P 8 Eliciting a dystonic phenotype in genetically predisposed rodents for DYT-TOR1A dystonia via an overuse paradigm. (May 2022) - Dubey, P.; Rauschenberger, L.; Knorr, S.; Grundmann-Hauser, K.; Ott, T.; Mendonca, M.; Costa, R.; Volkmann, J.; Ip, C.W.
Abstract : Introduction: Abnormal postures or movements caused by sustained or intermittent muscle contractions typically characterize the hyperkinetic movement disorder dystonia. DYT-TOR1A dystonia is the most common form of monogenic dystonia and follows an autosomal dominant pattern of inheritance. Although a trinucleotide deletion in the torsinA encoding gene, TOR1A, forms the genetic basis of this disorder, its reduced penetrance of 30-40% suggests the presence of disease modifying factors. Indeed, the induction of task specific forms of dystonia such as musician's dystonia and writer's cramp upon repetitive peripheral limb overuse lends strong support to a "second-hit" hypothesis, which states that exposure to environmental triggers could result in overt manifestation of dystonia in mutation carriers. Based on the hypothesis that an environmental trigger in the form of repetitive limb overuse induces dystonia-like movements in asymptomatic, but genetically predisposed rats expressing mutant human TOR1A, we have been working towards developing a clinically relevant model of dystonia. Materials and methods: Rats overexpressing mutant torsinA protein (ΔETorA) and their wildtype (wt) littermates were trained to perform a single-limb overuse task. The animals learned to press a lever by receiving a sugar water reward for each successful press in an operant testing chamber. Two overuse protocols were tested: 1000 presses/day, 6 days/week and 2000 presses/day, 3 days/week. Results: 1000 presses/day, 6 days/week did not affect motor performance of ΔETorA rats compared to the wt control group. In contrast, 2000 presses/day, 3 days/week over 5 weeks resulted in pronounced differences between wt and ΔETorA animals. Wt rats showed a consistently high success rate of ∼80% for pressing the lever. The velocity of forelimb movement and the accuracy in hitting the lever remained on a stable level. ΔETorA rats, however, were increasingly and significantly less successful at pressing the lever (∼75%) as compared to their wt littermates over the observational period. In addition, the average velocity of the movement towards the lever was shown to be reduced in the ΔETorA group compared to wt animals. Moreover, ΔETorA animals needed more trials to successfully hit the lever for the first time in a series of presses. Discussion/Conclusion: Our results indicate that the 1000 presses, 6 days/week protocol is insufficient to induce behavioural changes. The 2000 presses, 3 days/week protocol revealed that ΔETorA rats show a lower success rate in pressing the lever, a lower average velocity of movement of the right forelimb and difficulties in hitting the target successfully compared to their wt littermates. This points towards motor abnormalities induced by the overuse paradigm in ΔETorA rats compared to the wt control group.